Simultaneous genotyping of microsatellite variations in HMOX1 and UGT1A1 genes using multicolored capillary electrophoresis - Jiraskova, Alena; Lenicek, Martin; Vitek, Libor (Clinical biochemistry, 2010)
OBJECTIVES: Our aim was to establish a reliable, rapid, and inexpensive method for the simultaneous genotyping of the HMOX-1 (heme oxygenase-1) and UGT1A1 (bilirubin UDP-glucuronosyltransferase) gene promoter variations. RESULTS: The HMOX1 (GT)(n) and UGT1A1 (TA)(n) gene promoter variations were determined by fragment analysis using a single duplex PCR, with different fluorescent dye-labeled primers; followed by multicolored capillary electrophoresis. CONCLUSION: This novel method provides simultaneous genotyping of key tandem repeat variations in the HMOX1 and UGT1A1 promoters.
Keywords: Reproducibility of Results; genotyp; Microsatellite Repeats; glukuronosyltransferasa; Electrophoresis, Capillary; Humans; Glucuronosyltransferase; Polymorphism, Single Nucleotide; lidé; elektroforéza kapilární; jednonukleotidový polymorfismus; Heme Oxygenase-1; hemoxygenasa-1; reprodukovatelnost výsledků; mikrosatelitní repetice; Genotype